STIMULASI GURU PADA PEMBELAJARAN BAHASA ANAK USIA DINI - Endah Silawati (UPI Kampus Cibiru, 2012)
Languange skill is one of important skills developed in early years of a child. It is more than a tool for communications; it is an avenue for creative expression and tools that humans use to communicate or share thoughts, ideas and emotions (Logan et al., 1972). Right stimulation from adult, in this case: parents, other family members or teachers is needed to developed this skill. Unfortunately, when a child comes to school he is too often told to sit down and to be quite at a time when the right kind of talking is the key to succsesful learning (Logan et al., 1972). This paper is a part of a study about the teachers’ stimulations in language learning at Kindergarten held in Bandung in 2010. One of the aims of the study is to analize whether the language stimulations done by the teachers in Kindergarten are suitable with the concept of language stimulations based on theory proposed by Yawkey, et al. (1981). Keywords: Language skills, teachers’ stimulations, early childhood